2018
DOI: 10.1371/journal.pone.0194216
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a weather-based warning system to advise fungicide applications to control dollar spot on turfgrass

Abstract: Dollar spot is one of the most common diseases of golf course turfgrass and numerous fungicide applications are often required to provide adequate control. Weather-based disease warning systems have been developed to more accurately time fungicide applications; however, they tend to be ineffective and are not currently in widespread use. The primary objective of this research was to develop a new weather-based disease warning system to more accurately advise fungicide applications to control dollar spot activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…For example, anthracnose is more likely to develop during periods of water stress, which occurs more frequently in situations of high air temperature, than when water is not limiting (Roberts et al, 2011). Additionally, models predicting dollar spot and brown patch indicate disease is most likely to develop during periods of warm air temperature and high relative humidity (Fidanza et al, 1996;Smith et al, 2018). In cooler regions with a limited window This article is protected by copyright.…”
Section: Fungicide Usementioning
confidence: 99%
“…For example, anthracnose is more likely to develop during periods of water stress, which occurs more frequently in situations of high air temperature, than when water is not limiting (Roberts et al, 2011). Additionally, models predicting dollar spot and brown patch indicate disease is most likely to develop during periods of warm air temperature and high relative humidity (Fidanza et al, 1996;Smith et al, 2018). In cooler regions with a limited window This article is protected by copyright.…”
Section: Fungicide Usementioning
confidence: 99%
“…Five action thresholds of the logistic regression model risk index (RI) were evaluated for accuracy in predicting dollar spot for each bentgrass cultivar ( Table 1). The first action threshold, which will be referred to as "RI 20%," used a risk index threshold of 20% for predicting dollar spot based on the findings from Smith et al (2018). Preliminary observations indicated that the negative slopes of the risk index were strongly associated with periods of inactive dollar spot and positive risk index slopes were strongly associated with increasing dollar spot.…”
Section: Evaluation Of Risk Index Action Thresholdsmentioning
confidence: 99%
“…The third action threshold combined the RI 20% and RI slope action threshold and will be referred to as "RI 20% + RI slope" hereafter. Smith et al (2018) speculated that the risk index action threshold may need to be adjusted from 20% to accurately schedule fungicide applications for host species or cultivars with varying levels of dollar spot susceptibility. Thus, the fourth action threshold evaluated adjusting the risk index-from 1 to 60% in 1% increments-to select a RI threshold associated with the maximum accuracy in predicting dollar spot for each cultivar ( Figure S1), and will be referred to as the RI max action threshold.…”
Section: Evaluation Of Risk Index Action Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations